2018
DOI: 10.1002/fes3.141
|View full text |Cite
|
Sign up to set email alerts
|

Iron and zinc levels in Vigna unguiculata (L.) Walp under varying phosphorus and fixed nitrogen treatment conditions

Abstract: Using phosphate fertilizer (particularly at high levels) to improve the phosphorus (P) level of soils during the cultivation of legumes and other cereals unfortunately has negative effect on the levels of micronutrients like zinc (Zn) in grains. This study and cowpea is also at the heart of the fight against micronutrient deficiency due to its ability to accumulate Fe and Zn in both grains and leaves (Mamiro, Mbwaga, Mamiro, Mwanri, & Kinabo, 2011).However, micronutrient-deficient soils are widespread; many mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 42 publications
(50 reference statements)
2
12
0
Order By: Relevance
“…Application of Zn containing fertilizers has been observed elsewhere to increased cowpea's grain Zn content and yield under integrated soil fertility management (Manzeke et al, 2017). Ayeni et al (2018) observed that some cowpea genotypes had a high content of Zn at all levels of P, a nding similar to our observation in this study where certain genotypes such as IT82E-18, UCR779, CB46, and IT97K-556-6 had increased grain Zn content with increasing supply of P in the growth environment. This was con rmed by the GGE biplots that displayed genotypes like 16 (IT89KD-288), 8 (Danila), and 22 (SAMPEA-9) with high grain Zn content under high soil P fertilization while genotypes like 3 (58-77), 21(SAMPEA-17), 22 (SAMPEA-9) and 23 (Sanzi) had stable grain Zn across all P levels.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Application of Zn containing fertilizers has been observed elsewhere to increased cowpea's grain Zn content and yield under integrated soil fertility management (Manzeke et al, 2017). Ayeni et al (2018) observed that some cowpea genotypes had a high content of Zn at all levels of P, a nding similar to our observation in this study where certain genotypes such as IT82E-18, UCR779, CB46, and IT97K-556-6 had increased grain Zn content with increasing supply of P in the growth environment. This was con rmed by the GGE biplots that displayed genotypes like 16 (IT89KD-288), 8 (Danila), and 22 (SAMPEA-9) with high grain Zn content under high soil P fertilization while genotypes like 3 (58-77), 21(SAMPEA-17), 22 (SAMPEA-9) and 23 (Sanzi) had stable grain Zn across all P levels.…”
Section: Discussionsupporting
confidence: 89%
“…While a more recent study on the impact of contrasting P rates and constant level of N fertilizers on iron and Zn contents of cowpea grains made a contrary observation. Ayeni et al (2018) observed that application of P alone at high rates do not signi cantly decrease the content of Zn and Fe on cowpea grains, but a combination of high P (60 kg/ha) and N was associated with reduced Zn content of the grains. The authors provided some explanation for this observation suggesting that the lack of decrease in Zn content when only high P rate was applied may be due to applied P being xed in certain soil compounds.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations